Analisis dan Strategi Untuk Mendukung Prospek Perdagangan Rumput Laut Indonesia - Rahmadini Payla Juarsa (Pusat Pendidikan dan Pelatihan Perdagangan, 2019)
The Indonesian seaweed trade is still dominated by dry seaweed, even though Indonesia's seaweed still has high prospects for development. The purpose of this study is to analyze and provide strategies for supporting the prospects of Indonesia's seaweed trade. In achieving this goal, we use qualitative desk study methods and SWOT analysis. The results showed that Indonesia's seaweed trade still shows the opportunity to increase high added value by prioritizing the trade of semi-finished products rather than dried seaweed. This is supported by the strength of Indonesian seaweed which has a large potential for cultivation, a high number of laborer, high consumption of domestic and foreign seaweed derivative products and the availability of sufficient technology and expertise. Those strengths used to seize high import market opportunities. The existence of a national seaweed development road map also helps create a better prospect for seaweed trade.